Science communication during the COVID-19 pandemic: experiences, challenges and expectations from the perspective of scientists in Austria - Lorenzoni, Nina; Hallsson, Lára R.; Flatscher-Thöni, Magdalena; Förster, Lina; Schusterschitz, Claudia (Frontiers in Communication, 2025)
The COVID-19 pandemic put science in the spotlight like no other event before, but also created room for uncertainties, misinformation, and speculation. We used a qualitative research design and conducted semi-structured interviews with 13 scientists from various disciplines in Austria to shed light on their experiences and challenges with science communication during the pandemic as well as wishes and expectations for science communication in the future. The challenges most frequently mentioned by scientists refer to a lack of time to engage in science communication, uncertainty due to insufficient training in science communication, dealing with discrepancies between scientific advice and political decisions, and public skepticism towards science. Although almost all interviewees reported personal attacks via email and social media after public appearances, they emphasized the importance of transparency and openness in science to build trust and public understanding of scientific processes, despite such attacks. From the scientists’ perspective future strategies should involve integrating science communication into university curricula and expanding scientific education in schools. Moreover, scientists ask for enhancing transparency in political decision making, explicitly distinguishing between scientific recommendations and political decisions. Scientists point out, that during the COVID-19 pandemic new transdisciplinary networks have been established, which have helped to improve and extend research collaboration past the pandemic and should therefore be maintained and developed in the future.